Seeking refuge : a graphic novel - Watts, Irene N. (Tradewind Books, 2017)
A young Jewish girl named Marianne Kohn arrives in Great Britain on the Kindertransport--she has been saved from Nazis before the outbreak of World War II. However, even in Great Britain, the hate she experiences in the Third Reich continues. When Marianne and hundreds of other children are evacuated to the country, she meets outcries of "Christ killer!" and "Dirty spy!" Then, the couple she is staying with tries to remake her in the image of their late daughter. Throughout, though, Marianne finds allies who help guard her and encourage her own resourcefulness.